2016
DOI: 10.1038/srep23173
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal transcriptome provides insights into early fruit development of tomato (Solanum lycopersicum)

Abstract: Early fruit development is crucial for crop production in tomato. After fertilization, the ovary undergoes cell division and cell expansion before maturation. Although the roles of regulatory signals such as hormone and carbohydrate during early fruit development have been studied, the spatial distribution and the sequential initiation of these regulatory signals still need to be explored. Using the tomato cultivar ‘Moneymaker’, we analyzed the transcriptome of the ovule and the ovary wall/pericarp dissected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 55 publications
(80 reference statements)
1
53
0
Order By: Relevance
“…In agreement with the Expression Atlas of Tomato Tissues, four transcriptomic analyses concerning tomato fruit set reported that relative to pre‐anthesis (−2 days postanthesis, DPA) (Tang et al ., ; Wang et al ., ) or anthesis (Pattison et al ., ; Zhang et al ., ), Sl AGL6 expression sharply declines in fertilized fruit at 4‐5DPA (Figure S4b,c,d). However, in unpollinated emasculated ovaries, it scarcely declined (by 1.4‐fold only, Figure S4b), suggesting that its decline following fertilization is inherent to fruit set.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…In agreement with the Expression Atlas of Tomato Tissues, four transcriptomic analyses concerning tomato fruit set reported that relative to pre‐anthesis (−2 days postanthesis, DPA) (Tang et al ., ; Wang et al ., ) or anthesis (Pattison et al ., ; Zhang et al ., ), Sl AGL6 expression sharply declines in fertilized fruit at 4‐5DPA (Figure S4b,c,d). However, in unpollinated emasculated ovaries, it scarcely declined (by 1.4‐fold only, Figure S4b), suggesting that its decline following fertilization is inherent to fruit set.…”
Section: Resultsmentioning
confidence: 92%
“…Yet 5DPA it sharply declines to the level found in ovaries of the young 4-mm-long flower buds, hence associating 'ovary arrest' with elevated SlAGL6 expression and fruit set with its decline. Genetic variation between M82 and Micro Tom or Solanum pimpinellifolium might explain the higher fold decline between anthesis and 4DPA reported before (Pattison et al, 2015;Tang et al, 2015;Wang et al, 2009), whereas smaller variation between M82 and Moneymaker could account for the observed similarity in fold decline (Figure 7 vs. Figure S4d, queried from Zhang et al, 2016). Evidence for preferential sublocalization of the SlAGL6 transcript within the ovules of the mature arrested ovary was provided by Pattison et al (2015).…”
Section: Slagl6 Mode Of Expressionmentioning
confidence: 81%
See 2 more Smart Citations
“…Xylene was replaced gradually with paraffin (Paraplast Plus, Sigma, P3683) at 60°C for two nights with four times replacement of paraffin. Ten μm sections were made using a HEISTION ERM3000 microtome and stained with Toluidine Blue O [23], and examined at x100 in a light microscope.…”
Section: Methodsmentioning
confidence: 99%